HUBUNGAN KEDISIPLINAN GURU TERHADAP HASIL BELAJAR SISWA DI SMK YPK PENGHARAPAN AIMAS KABUPATEN SORONG - Yunus Aisnak; Sirojjuddin; Jaharudin Jaharudin (Adisam Publisher, 2025)
This study aims to determine the relationship between teacher discipline and student learning outcomes at SMK YPK Pengharapan Aimas in Sorong Regency. This study used a quantitative research design with a correlational approach. The study involved 20 tenth-grade students as samples, selected through purposive sampling. Data collection was conducted using a teacher discipline questionnaire and documentation of student learning outcomes. The collected data were analysed using Pearson's correlation test. The results showed a significant positive relationship between teacher discipline and student learning outcomes, with a correlation coefficient of 0.645, indicating a fairly strong influence. Teacher discipline in managing time, arriving on time, and consistency in giving assignments and evaluations played a major role in improving student learning outcomes. The researchers recommend that teacher discipline continue to be improved to encourage better student learning outcomes, as well as the importance of cooperation between teachers and students to create a conducive learning atmosphere.